The last battle - Lewis, C. S. (Clive Staples), 1898-1963.; Stewart, Patrick, 1940- (New York : Harper Children's Audio, 2004)
Tirian, the last king of Narnia, is forced to make a stand against an Aslan imposter who raises forces both from within the land and without. Jill Pole and Eustace Scrubb are summoned to Narnia to help and ultimately to witness the last events.
Compact disc.
Unabridged.
Performed by Patrick Stewart.
890
Accelerated Reader AR
Keywords: Narnia (Imaginary place) -- Juvenile fiction; Narnia (Imaginary place) -- Fiction; Fantasy; Audiobooks; Children's audiobooks; Fantasy fiction